Mosaic diamond detectors for fast neutrons and large ionizing radiation fields. Issue 11 (18th June 2015) - Girolami, Marco; Bellucci, Alessandro; Calvani, Paolo; Cazzaniga, Carlo; Rebai, Marica; Rigamonti, Davide; Tardocchi, Marco; Pillon, Mario; Trucchi, Daniele M.
Abstract : First neutron and X‐ray beam tests on a novel 12‐pixel single‐crystal diamond mosaic detector are presented and discussed. Preliminary characterization of single‐pixel electronic properties, performed with α particles, results in charge carrier mobilities >2000 cm 2 Vs −1 and saturation velocities of the order of 10 7 cm s −1 . Signal stability over time, measured with a 241 Am source (37 kBq activity), is longer than 5 h. Tests under an intense X‐ray beam (1 Gy h −1 dose‐rate) show a very good response uniformity (down to about 1% of relative standard deviation from mean value), suggesting a high level of pixel reproducibility at intermediate bias voltages (ranging from 20 to 100 V). Response uniformity reduces at voltages >200 V, due presumably to radiation‐assisted detrapping effects. Preliminary results of 12‐pixel simultaneous acquisitions of X‐ray beam profiles and pulse height spectra under a fast neutron beam (14 MeV) are also presented.